Operational Risk Management Case and Proposed Action Plan to Support Business Continuity at PT. Freeport Indonesia - Yurizal, Ruky; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2015)
Abstract- Internal and external environmentalsituation changes and the company experienced  rapid growth followedby the increasing complexity of risk and its uncertainty in the operational activities undertaken by the company. This final project will focus on the issue of managing thepotentialriskof people at PT Freeport Indonesia, which could have an impact on mining activities and the delay resulted in the cessation of production activities as well as a reduction in the production of normal production capacity. Risks that have been and will be faced by PT Freeport  Indonesia can be affectingto Business Continuityin the futureand also could affect the potential problems and risks that might appear, therefore,to minimize any potential risks that may arise in the operational  activities,this  paper  will focus on how to implement the  Operational Risk Management  by emphasizing to people risk in regards to minimize and preventrisk to the operational activitiesof the company. The research comprisesof an analysis of the existing literature within the scope of Operational Risk Management and exploration of Risk Managementpractice that has beenapplied in the PT FreeportIndonesia today. The research approach is also through by benchmarking  against practices of Operational Risk Management at the company that has implemented  so in order to find and assess best practices that can be applied to the PT Freeport Indonesia. The research  data is predominantly  qualitative.  On the implementationof the Operational  Risk Managementplan will follow the rules of the sequence of steps Risk Managementby the accompaniment of Management commitment  and all organizational linesto make  risk managementand business continuity managementas a whole culture in the implementation  of the company's operation in preventing the impact of the risk without reducing the opportunity of corporate objectives to be achieved. Keywords: Risk, People Risk, Business Continuity, Operational Risk Management, Risk Management Abstract- Internal and external environmentalsituation changes and the companyexperienced  rapid growthfollowedby the increasing complexity of risk and its uncertainty in the operational activities undertaken by thecompany. This final project will focus on the issue of managing thepotentialriskof people at PT FreeportIndonesia, which could have an impacton mining activitiesand the delay resultedin the cessation of productionactivitiesas well as a reduction in the production of normal production capacity. Risks that have been and will befaced by PT Freeport  Indonesia can be affectingto Business Continuityin the futureand also could affect thepotentialproblems and risks that might appear,therefore,to minimizeany potentialrisks that may arise in theoperational  activities,this  paper  willfocus on how to implementthe  OperationalRiskManagement  byemphasizing to peoplerisk in regards to minimize and preventrisk to the operationalactivitiesof the company.The research comprisesof an analysis of the existing literaturewithin the scope of Operational Risk Managementand exploration of Risk Managementpractice that has beenapplied in the PT FreeportIndonesia today. Theresearchapproach is also through by benchmarking  against practices of OperationalRisk Management at thecompany that has implemented  so in order to find and assess best practices that can be applied to the PT FreeportIndonesia. The research  data is predominantly  qualitative.  On the implementationof the Operational  RiskManagementplan will follow the rules of the sequenceof steps Risk Managementby the accompaniment ofManagementcommitment  and all organizational linesto make  risk managementand business continuitymanagementas a whole culture in the implementation  of the company's operation in preventing the impact ofthe risk without reducing the opportunity of corporate objectives to be achieved.Keywords: Risk, People Risk, Business Continuity, Operational Risk Management, Risk Management